Evaluasi Pengelolaan Lansekap Areal Vila Obyek Wisata Bagus Agro Pelaga, Kabupaten Badung - SAPUTRA, I MADE SUARJAYA DWI; SUGIANTHARA, A.A. GEDE; LILA, KOMANG ARTHAWA (Jurnal Arsitektur Lansekap; Vol.2, No.1, April 2016, 2016)
Evaluation of the Management Landscape in Bagus Agro Pelaga Vila Area, Badung Regency Landscape management it is really needen in the progress of Bagus Agro Pelaga (BAP) to improve tourism industry. The best landscape management and suistinable be able give more valve into development agrotourism and satisfaction to the guest. Landscape management is focused in this study only landscape management villa area. Purpose from this reseach is to know the consept of manage the landscape villa area which is used at BAP, know as technical orientation in managed landscape villa area in BAP, to analyst stemulation factor and brominated factor which is influence managerial activity landscape villa area in BAP. Reseach result indicate that planing most important program on the concept which is applied BAP for that villa mentioned already 80% appropriate. That is, what wash already planning appropriate with first purpose or first design. Base which is be orientation for landscape villa area in BAP is blend with concept terracing garden also management system which is democratic. The factor which is influence management landscape activity in BAP that is from internal factor such us, the necessity of SOP, increasing employee specially aesthetics employee on the villa area BAP, and the equitment isn’t enough. External faktor review input from the visitor and obserb on location suck as, amount of plants , structuring and treatment of the plants, the occurrence of vandalism, cleanliness of the pool, not enough of garbage bin, garden bench, ganden lamp, and long chair. Keywords : park management, park maintenance